2021
DOI: 10.7150/ijbs.62767
|View full text |Cite
|
Sign up to set email alerts
|

The functional roles, cross-talk and clinical implications of m6A modification and circRNA in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related deaths worldwide. HCC has high rates of death and recurrence, as well as very low survival rates. N6-methyladenosine (m6A) is the most abundant modification in eukaryotic RNAs, and circRNAs are a class of circular noncoding RNAs that are generated by back-splicing and they modulate multiple functions in a variety of cellular processes. Although the carcinogenesis of HCC is complex, emerging evidence has indicated that m6A modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 162 publications
(189 reference statements)
1
30
0
Order By: Relevance
“…However, conventional HCC treatments, including surgical resection and transplantation, are only effective in patients diagnosed at early stages 3 . HCC is characterized with abnormal expression of a lot of genes 4 - 6 , which results in frequent occurrence and distant metastasis of tumor as well as poor prognosis of HCC patients 7 , 8 . So far, there is no particularly effective therapeutic options for advanced HCC patients 9 .…”
Section: Introductionmentioning
confidence: 99%
“…However, conventional HCC treatments, including surgical resection and transplantation, are only effective in patients diagnosed at early stages 3 . HCC is characterized with abnormal expression of a lot of genes 4 - 6 , which results in frequent occurrence and distant metastasis of tumor as well as poor prognosis of HCC patients 7 , 8 . So far, there is no particularly effective therapeutic options for advanced HCC patients 9 .…”
Section: Introductionmentioning
confidence: 99%
“… 49 , 50 Based on the available reports, we found that different m6A-related factors are differentially expressed or functionally inconsistent in HCC, which may stem from the different biological functions triggered by the signalling pathways affected by the different downstream targets of m6A. 51 However, there is no research on the relationship between KRBA1 and m6A in tumors. Our results found a strong positive correlation between KRBA1 m6A modification and gene expression, especially for the five genes IGF2BP2, METTL3, YTHDF1, RBM15B, and HNRNPA2B1.…”
Section: Discussionmentioning
confidence: 98%
“…As the main subtype of primary liver cancer, HCC comprises 75–85% of cases, which is one of the leading causes of cancer-related deaths worldwide [ 46 ]. In recent years, accumulating evidence has confirmed that circRNAs and m6A, especially their interplays, play key roles in many aspects of HCC [ 190 ]. For instance, METTL3 and YTHDC1 were uncovered to promote circHPS5 generation and cytoplasmic export in HCC, respectively.…”
Section: The Interplay Between M6a Modification and Circrnas In Cance...mentioning
confidence: 99%
“…With the accumulation of epigenetic studies, it has been gradually realized that aberrant epigenetic modifications of RNA, especially m6A modification may result in HCC occurrence, progression and even therapeutic resistance [ 190 ]. YTHDF1 belongs to the YTH domain family, which is responsible for the modulation of RNA translation.…”
Section: The Interplay Between M6a Modification and Circrnas In Cance...mentioning
confidence: 99%